PUBLIC RELATIONS: THE KEY TO ENHANCING UNIVERSITY GLOBAL RANKINGS AND REPUTATION (Scientific journal of the Fergana State University, 2024)
In the competitive landscape of higher education, a university's reputation and global ranking are crucial factors influencing student admissions, attracting qualified faculty, and fostering institutional collaboration. This article examines the decisive role of public relations (PR) in managing and strengthening university reputation. It explores effective PR strategies that can be utilized to create a positive image for universities, enhance global visibility, and build trust among key stakeholders. The importance of utilizing mass media to showcase university achievements, engage with the public, and strengthen the university brand on an international scale is emphasized. Additionally, practical recommendations for leveraging PR tools to achieve sustainability, enhance reputation, and improve positions in global rankings are provided.